Differential impact of working hours on unmet medical needs by income level: a longitudinal study of Korean workers - Lee, Dong-Wook; Choi, Jaesung; Kim, Hyoung-Ryoul; Myong, Jun-Pyo; Kang, Mo-Yeol (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVES ': 'Unmet medical need is defined as the perceived need for medical service that is not received. Although the association between unmet medical needs and working hours has been explored before, the combined effect of household income has not been investigated thus far. This study, therefore, aimed to examine the differential association between working hours and the risk of unmet medical needs according to household income. ' ' METHODS ': 'A total of 7047 participants enrolled in the Korea Health Panel data 2011–2014 were considered. The analytical method used in this study was a generalized estimating equation model that accounted for repeated measured participants. By controlling for time-invariant individual-fixed effects, we identified the relationship between long working hours and the risk of unmet medical needs. ' ' RESULTS ': 'The association between long working hours and the risk of unmet medical needs differed according to household income. In the highest quintile of household income, the risk of unmet medical needs was 1.58-fold higher among those who worked >52 hours per week than among those who worked 30–52 hours per week. However, this association was not significant in the lowest quintile group. ' ' CONCLUSIONS ': 'The current study implies that financial hardship might be a more fundamental health hazard than working longer hours among the low-income group. Future policies should consider not only limiting working hours but also compensating workers’ income to adequately protect low-income workers from the health risks associated with long working hours.
Keywords: health inequity; income level; Korean worker; longitudinal study; unmet medical need; working hour